The experience of mission hospitals in southern Ethiopia in identifying and responding to infectious disease outbreaks - Bernt Lindtjørn; Thor Henrik Henriksen (Health for All Nations, 2020)
Epidemics are often seen at mission health institutions. Such Christian institutions seek to practice holistic medicine, and the core priorities include dedicated clinical care combined with community responsibility. This paper describes some unusual, and some more common, epidemics that occurred at three mission hospitals in Southern Ethiopia during the last 60 to 70 years. The hospitals covered vast areas and large populations, mostly from poor subsistence farming communities. With great topographical and climatic variations, the catchment areas include multiple climate zones that cause substantial variations in ecology and vegetation, and thus, also in disease patterns. Our review is based on personal notes, hospital records, and previous scientific publications.